뉴로피드백을 이용한 명상훈련이 정상 성인의 기억과 집중력에 미치는 영향 - 정선용; Sun Yong Chung; 서진우; Jin Woo Seo; 김종우; Jong Woo Kim; 황의완; Wei Wan Whang (동의신경정신과학회지, 2008)
Objective : The objective of this study was to investigate the effects of breath meditation with neurofeedback on memory, concentration of healthy adult volunteers. Method : 25 healthy adult volunteers were divided into two groups. One group was treated with breath meditation and real neurofeedback, but the other group was administered with breath meditation and sham neurofeedback three times a week for 10 sessions. Before and after 10 sessions neurofeedback, all subjects were measured by cognitive functions assessment, heart rate variability, BDI, STAI, K-WAIS, HRSD, VAS about amnesia. Results : 1. Breath Meditation decreased error rate and increased concentration, cognition strength, and success rate of Cognitive Functions Assessment. Also, Breath Medication elevated IQ score of K-WAIS short form. 2. Sham neurofeedback increased concentration, cognition strength compared to Real neurofeedback. Conclusion : The results suggest that breath meditation might effect cognitive function of healthy adult positively, but neurofeedback is not clear. In order to prove whether neurofeedback is effective or not, it should be studied more.